Health inequality over the life-cycle - Timothy J. Halliday (Institute for the Study of Labor (IZA), 2009)
We investigate the evolution of health inequality over the life-course. Health is modeled as a latent variable that is determined by three factors: endowments, and permanent and transitory shocks. We employ Simulated Minimum Distance and the Panel Study of Income Dynamics to estimate the model. We estimate that permanent shocks account for under 10% of the total variation in health for the college educated, but between 35% and 70% of total health variability for people without college degrees. Consistent with this, we find that health inequality moves substantially more slowly over the life-course for the college educated.
urn:nbn:de:101:1-2009100235
Keywords: I1; C5; 330; Health; dynamic panel data models; variance decomposition; Gesundheit; Lebenszyklus; Soziale Ungleichheit; Bildungsniveau; USA